Tandem Autologous Stem Cell Transplantation for Multiple Myeloma Patients Based on Response to Their First Transplant—A Prospective Phase II Study. (January 2014) - Byrne, Michael; Salmasinia, Donya; Leather, Helen; Cogle, Christopher R.; Davis, Amy; Hsu, Jack W.; Wiggins, Laura; Chang, Myron N.; An, Qi; Wingard, John R.; Moreb, Jan S.
In this prospective phase II clinical trial, multiple myeloma (MM) patients were randomized to receive a second (tandem) autologous stem cell transplantation (ASCT) based on whether they achieved a partial response or worse (≤PR) following initial ASCT (ASCT1). Patients who achieved a very good partial response or better (≥VGPR) had salvage ASCT at relapse. Seventy-five patients received conditioning therapy and ASCT1. A total of 44 patients (59%) achieved ≥VGPR, whereas 31 patients entered ≤PR and were offered tandem ASCT. In all, 20 patients agreed to tandem ASCT. Demographic and clinical characteristics were similar between the two cohorts except for median lactate dehydrogenase (LDH) ( P = 0.0141) and percentage of marrow plasma cells before ASCT1 ( P = 0.0047), both lower in the ≥VGPR group. Intent to treat analysis showed that patients who achieved ≥VGPR to ASCT1 had a trend toward improved progression-free survival (PFS) (37 vs. 26 months, P = 0.078) and superior overall survival (OS) (not reached vs. 50 months, P = 0.0073). Patients with ≤PR who declined tandem transplantation had shortened PFS (20 vs. 28 months, P = 0.05) but similar OS (53 vs. 57.5 months, P = 0.29) compared to those who received it. Thus, a favorable clinical response to ASCT1 identifies a low-risk group with superior long-term prognosis despite similar PFS.